Isolamento e identificação de bactérias alcalifílicas associadas aos resíduos de bauxita - Alves, Enne Gomes (2014)
The bauxite waste represents an important environmental liabilities due to the risks to the environment associated with high alkalinity and management costs and disposal. As little is known about the establishment of microbial populations in these disposal sites of bauxite residue, the objective of this study was to isolate and identify microorganisms present in samples from a deposit located in the region of Pocos de Caldas, Minas Gerais. Therefore, samples were collected from the depths of 0.25, 0.50 and 1 m and from drain water and inoculated in alkaline medium (pH 10.5) for enrichment cultures, for growing under aerobic and anaerobic conditions and isolation strains from enriched cultures. The isolated strains were examined by light microscopy, PCR, DGGE and partial sequencing of the 16S rRNA gene. 6 strains were isolated of bacteria under aerobic conditions (at a depth of 2). The 6 isolates showed bacillary form, Gram-positive staining, and the analysis of sequencing indicated that all belong to the genus Bacillus and correlate the three distinct groups alcalifílicos with a high degree of identity: the A1 and A2 strains (0.25m deep) with Bacillus cohnii; strains B1, B2 (0.50m) and C2 (1m) with Bacillus pseudofirmus; and the C1 strain (1m) with Bacillus clarkii and Bacillus polygoni. The present results show the enrichment and the successful isolation of alkaliphilic bacteria waste of bauxite, which will allow further study of the same and better understanding of this extreme environment.